Language Education for Development: Enhancing Regional Banks' Performance through Illocutionary Speech Act Mastery in Indonesia - Sunendar, Dadang; Erlina, Erlina; Sundari, Sri; Hardini, Tri Indri; Maulana, Cepri; Sunendar, Neidya Fahma (Universitas Negeri Makassar, 2024)
This study aims to explain how language plays a significant role in improving the performance of regional development banks in Indonesia. The method used was qualitative with a questionnaire instrument involving 6 regional development banks in Indonesia. Some of the main findings are 24 statements were found, 19 of which fall into 5 categories, namely assertive illocutionary speech acts, directive illocutionary speech acts, expressive illocutionary speech acts, commissive illocutionary speech acts, and declarative illocutionary speech acts. In its implementation, the process emphasizing the humanistic approach scored over 90%. By prioritizing language training initiatives that emphasize the mastery of illocutionary speech acts, regional banks in Indonesia can expect improved operational efficiency, strengthened customer relationships and a more strategic approach to communication, contributing to the overall development and success of the banking sector. This study is limited to the context of only one type of bank, the regional development bank. It is further suggested that there is a strong need to provide adequate and timely capacity building for the employees of regional development banks, particularly in language training as part of public service and satisfaction development.